Katie McNaught: capstone - McNaught, Katie, artist (Colorado State University. Libraries, 2021)
The artist's statement: My relationship with my family, my heritage, and my own past life are very complicated. Common themes that made an appearance throughout my formative years include divorce, abuse in every sense of the word, purity culture, and general religious trauma. I feel like my childhood and teenage years were stunted in many ways as a result of the actions of my family and the things I had to see and live through while I was still a developing kid, like I had to grow up much sooner than everyone around me. I'm painting my upbringing and familial ties to be somewhat of a nightmare (sometimes it definitely was), but I also had a fairly normal childhood and family dynamics in many ways, and have a lot of nostalgia for the things missing from my past or that were severed from me later in life. And while I still dread going to family get togethers because of the dinner table conversation, I still love my family, and I still see a lot of strength and beauty in their lives. Work with fibers has been a common theme throughout the women on my mom's side as a means of survival and expression. I learned to sew from my grandma, and crochet from my great grandma. My grandma made my mom's clothes as a kid as well as her bridal veil. My great grandma crocheted us baby blankets, stuffed animals, and worked in a sewing factory in the early 1900s. Her mother before her sewed quilts made out of depression-era flour bags the we still have in our house. The matrilineal passing of knowledge and skill has been something that's been present throughout many aspects of my life and manifests strongly within fibers. The subjects of matriarchy, family lineage, and the concept of heirlooms and hereditary passing are common themes that appear throughout my work in many different forms. My work varies widely in composition, materials, and techniques used, but there's a strong emphasis on embroidery and sewing throughout many pieces. My emotions relating to my family, religion, and marriage are complex and conflicting. Making art that explores these different aspects helps me to come to terms with the past, heal, and process my feelings in different ways.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers